Manual of Sedimentary Structures [Bulletin (Australia. Bureau of Mineral Resources, Geology and Geophysics), 102. ] - Crook, K A W (Canbera:Australia Centre for International Agricultural Research, 1982)
Koleksi Referensi (Tidak Dipinjamkan)